2012
DOI: 10.1111/aas.12028
|View full text |Cite
|
Sign up to set email alerts
|

CNAP® does not reliably detect minimal or maximal arterial blood pressures during induction of anaesthesia and tracheal intubation

Abstract: The CNAP monitor could detect acute change in AP within a reasonable time lag. Precision of its measurements is not satisfactory, and therefore, it could only serve as a clue to the occurrence of changes in AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…deep hypotension following anesthesia induction etc.). The trending ability remained unaffected by these inaccuracies [ 24 , 25 ]. In addition, as pointed out by Hahn [ 22 ], the device uses the oscillometric cuff as a reference, making it equivalent to contemporary practice in the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…deep hypotension following anesthesia induction etc.). The trending ability remained unaffected by these inaccuracies [ 24 , 25 ]. In addition, as pointed out by Hahn [ 22 ], the device uses the oscillometric cuff as a reference, making it equivalent to contemporary practice in the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Regarding the accuracy of blood pressure recordings in comparison to continuous invasive measurements, the results are conflicting. [9][10][11] With respect to PPV CNAP , Monnet and colleagues 12 were able to show that PPV was valuable in predicting FR in critically ill patients on the ICU; however, the values were calculated offline. Recently, a 'grey zone' approach has been introduced in order to assess more clearly the inconclusive values of dynamic variables around a defined cut-off value, helping to optimize fluid resuscitation on the basis of dynamic variables.…”
mentioning
confidence: 99%
“…3,15 However, Gayat and associates showed that CNAP rapidly reflected changes in blood pressure but failed to be in concordance with arterial pressure measurements. 16 Ilies and associates showed in another study that measurements obtained by CNAP at different stages of anesthesia were unreliable. 12 In our study, CNAP was used in living donors during liver transplant for liver transplant.…”
Section: Discussionmentioning
confidence: 99%